UPAYA PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN POTENSI GEOLOGI DESA BOTUBARANI, KABUPATEN BONE BOLANGO - Permana, Aang Panji; Aris, Ayub Pratama; Ninsafitri; Masruroh; Pambudi, Moch Rio; Hidayansya, Taufik (Journal of Community Services on Multidisciplinary Sciences, 2023)
Botubarani Village has great potential for geosite development in the Tomini Bay area, through community empowerment efforts, it is hoped that the Botubarani Village community can become an active part in the geosite development process in the Tomini Bay area. The method of implementing KKN MBKM to build villages starts from technical briefing to work program action. Students focus on field observations and interviews, in addition there are mandatory programs and community empowerment programs. The results of the mapping activities carried out produce an output in the form of maps. The results of the community empowerment program are carried out by fixing all damaged geosite infrastructure, as well as socializing to the community about tourism management. This activity involves personnel from the Botubarani Village community who have been actively involved in various stages of geosite development, from potential identification, planning, to promotion. Their participation proves that community empowerment is the main key to success in sustainable geosite development. Hopefully, it can create a broad positive impact on the community, the environment, and sustainable development in general.